Estudo do comportamento PTCR em cerâmicas de BaTiO3 : la sinterizadas a laser - Silva, Marcelo Souza da (2014)
The present work aimed to laser sintering and physical characterization of barium titanate ceramics doped with lanthanum, Ba1-xLaxTiO3 (0.1 ≤ x ≤ 0.4) mol%, and co-doped with manganese, in order to study the PTC effect (Positive Temperature Coefficient of Resistance). In electrical and electronic equipments, materials that exhibit PTC effect are generally used in circuit protection, or as temperature sensors (thermistors), whose main advantages of thermistors are no contacts subject to corrosion, high resistance to mechanical shock, the long operating life, low cost and more stable than thermocouples. Additionally, the laser sintering process uses a CO2 laser as the main heating source. This process has been touted as a promising technology for the ceramic processing, which are subjected to extremely high heating and cooling rates (~ 2000 ° C / min). During the processes of synthesis and characterization Differential Thermal Analysis (DTA), Thermogravimetry (TG), Dilatometry, Differential Scanning Calorimetry, X-ray Diffraction, Scanning Electron Microscopy, Impedance Spectroscopy and Conductive Microscopy Atomic Force (CAFM) technique were used. Lanthanum doped barium titanate powders were produced via solid state reaction method and calcined at 1200 ° C for 4 hours. The laser sintering process was efficient to obtain ceramics with relative density of up to 95%. The sintered ceramics presented homogeny microstructure surface under the condition of Pmax = 5.5 W/mm2 for 60 seconds. The 02BT La sample showed the lowest room temperature resistivity (104 .cm). This value is roughly three orders of magnitude lower than that observed for conventionally sintered ceramic in electric furnace and with the same dopant concentration. Finally, it is clear that the sintering conditions strongly modify the PTC behavior of the like-BaTiO3 ceramics, thus allowing the fabrication of ceramic components for the thermistors manufacture with different characteristics.